Layered ZnIn2S4 Single Crystals for Ultrasensitive and Wearable Photodetectors. Issue 21 (21st August 2021) - Valdman, Lukáš; Mazánek, Vlastimil; Marvan, Petr; Serra, Marco; Arenal, Raul; Sofer, Zdeněk
Abstract: Zinc indium sulfide belongs to the family of layered ternary chalcogenides. Although ZnIn2 S4  has a suitable bandgap in the visible range, its optoelectronic properties are not fully investigated. Most photodetectors based on layered semiconductors suffer from large dark currents, which hamper their performance and energy efficiency. In this work, high quality ZnIn2 S4 single crystals are synthesized via chemical vapor transport. The free‐standing crystals are ≈20 μm thick and up to 2 cm 2 in area and produce large photocurrents upon UV–vis illumination, while also maintaining extremely low currents in the dark. This allows to fabricate a simple photodetector with ohmic contacts, exhibiting extremely small dark currents down to 10 –12  A. The ON/OFF (light/dark) switching ratio reaches value of 10 6, the highest reported for a layered semiconductor. Furthermore, the photodetector exhibits remarkable responsivity of 173 A W –1 and excellent detectivity of 1.7 × 10 12 Jones. To demonstrate sensitivity and flexibility of the ZnIn2 S4 crystals, a wearable device is also fabricated. The wearable is able to record human heart rate and compare it with signal measured by a commercial smartwatch. The results suggest a substantial research potential in further explorations of ZnIn2 S4 and other ternary chalcogenides for optoelectronic applications. Abstract : In this work, high quality ZnIn2 S4 single crystals are synthesized via chemical vapor transport. The crystals produce large photocurrents upon UV–vis illumination, while also maintaining extremely low dark currents (≈10 –12  A). The ON/OFF switching ratio reaches a value of 10 6, the highest reported for a layered semiconductor.